Promoting Better Hand off and Achieving Better Patient Care in ICU (Bangladesh Critical Care Journal, 2013)
DOI: http://dx.doi.org/10.3329/bccj.v1i2.17196 Bangladesh Crit Care J September 2013; 1 (2): 63-64